(untitled) (Моделювання, керування та інформаційні технології, 2019)
This work is devoted to design, development and practical implementation of an AR application for simulation and programming of an industrial robot basic movements. The process of the AR-based application for mobile devices is briefly described to show the advantages and scalability of the proposed concept.